Consumers’ intention to use mobile health applications from the consumer acceptance technology (CAT) perspectives - Nazlin Kamaruzaman, Khairul; Fikry, Amily; Hussein, Zuhal (International Journal of Engineering and Technology, 2018)
In this millennium era, people are easily infected with the disease. Noting that the advancement of technology and the high user of the smartphone, people may use the applications provided in smartphone specifically for healthcare management as a step to avoid infected disease. This study attempts to investigate the relationship between perceived cognition, perceived affect and behavioral intention to use mobile health applications from the consumer acceptance technology (CAT) perspectives. This is a non-experimental study, whereby data was collected from non-probability sampling using purposive sampling. The individual recruited to be the sample are those who are owned at least a smartphone (n=30). The result indicates that the overall relationships between antecedences tested in this study perceived cognition (perceived ease of use, perceived usefulness, and relative advantage), perceived affect (pleasure, arousal, and dominance) are significant towards the behavioral intention to use mobile health applications.Â